Characterising exoplanet atmospheres: Bayesian techniques for transit lightcurves - Evans, T (2014)
Precise measurements of transit lightcurves can be used to constrain the composition and structure of exoplanet atmospheres. Unfortunately, efforts to extract this information are usually hampered by the presence of correlated noise that is degenerate with the astrophysical signal of interest. A major theme of this thesis is the application of robust analysis methods to properly account for such degeneracies. In particular, I advocate the use of Bayesian inference for lightcurve fitting. For this study, the Bayesian framework is exploited by modelling lightcurves as Gaussian processes (GPs), which offer numerous advantages over traditional decorrelation methods. The main advantage is that GPs do not require a functional form to be specified for the poorly understood lightcurve systematics. Instead, the high-level properties of the signal covariance are parameterised, allowing complex correlations to be marginalised over relatively low-dimension parameter spaces. I use GP models to analyse transit and eclipse lightcurves for the hot Jupiters HD189733b, HD209458b, and HAT-P-32b. The work is spread over three separate projects. Firstly, I re-analyse the majority of the transits and eclipses that have been observed using the Spitzer Space Telescope Infrared Array Camera (IRAC) for HD189733b and HD20945b. The GP analyses generally produce uncertainties for inferred planet parameters that are factors of ~1-5 larger than those quoted in the literature. In a number of cases, I obtain results that are fundamentally different to those published previously, with significant implications for the understanding of the atmospheres. Secondly, I report an eclipse observation for HD189733b that was made using the Hubble Space Telescope (HST) Space Telescope Imaging Spectrograph (STIS) over the 290-570nm wavelength range. Geometric albedos of Ag=0.37+12-13 and Ag=0.37+13-12 are measured in the wavelength ranges 290-450nm and 450-570nm, respectively. This represents the first ever multi-wavelength eclipse measurement made for an exoplanet at visible wavelengths. The nonzero albedo in the 290-450nm wavelength channel provides evidence for scattering in the atmosphere, possibly by haze/clouds or H2 molecules. The relatively low albedo in the 450-570nm wavelength channel is interpreted as being due to absorption by the wings of the Na 589nm doublet. Thirdly, I present two transit observations for HAT-P-32b made using the Nordic Optical Telescope (NOT) Andalucia Faint Object Spectrograph (ALFOSC) in multi-object spectroscopy mode over the 414-702nm wavelength range. A joint GP model is fit to the two white lightcurves produced by integrating the spectra over the full wavelength range. Spectroscopic lightcurves are also generated by binning into 32nm-wide wavelength channels, and preliminary lightcurve analyses are performed. The extracted transmission spectrum shows some evidence for absorption features, but this interpretation is currently very tentative. Further refinements to the data reduction and lightcurve analysis are suggested, which will allow the transmission spectrum to be evaluated more definitively.